Forage quality and NPK uptake of Napier Bajra hybrid as influenced by different planting material and weed infestation durations - Gill, Prabhsimran Kaur (Indian Journal of Animal Nutrition, 2018)
A field experiment was conducted to investigate the forage quality and NPK uptake of NBH (Pennisetum purpureumÃ—Pennisetum glaucum) as influenced by different planting material and weed infestation durations at forage research farm, Punjab Agricultural University, Ludhiana, India during 2014 and 2015. The experiment was laid out in split plot design keeping two planting material (root slips and stem cuttings) in main plot and weed infestation durations (weed infested till initial 10, 20,30, 40 and 60 days after planting and weed free for initial 10, 20, 30, 40 and 60 days after planting) in sub plot. The quality parameters of crop were significantly improved by keeping the crop weed free from 10 to 30 days after planting. The NPK uptake of Napier Bajra hybrid was significantly increased in crop planted with root slips than stem cuttings and in treatments kept weed free throughout the season that was at par with crop kept weed free for 40 days, for 30 days and kept weedy for 10 days during both years.Â Â